TRANSFORMASI PRODUKTIVITAS MAHASISWA PENDIDIKAN SOSIOLOGI UNTIRTA DI MASA PANDEMI - Haerullah, Fiqri Alamsyah; Kudus, Wahid Abdul (Universitas Tanjungpura, 2022)
This study aims to examine in depth how the productivity transformation of Untirta Sociology Education students during a pandemic when lectures are carried out online; this study will find out what productive activities are carried out during the pandemic and the factors and goals in carrying out these activities, which is then analyzed with the glasses of James Coleman's rational choice theory. This study uses a qualitative method with a descriptive approach. The source of the data in the survey is active students of Sociology Education Untirta. They have run the lecture process online and offline at the time before the entry of the pandemic. The data in this study were obtained through observation, interviews, and documentation techniques with a random sampling technique. The results of this study are that there was a change in the productivity of Untirta Sociology Education students during this pandemic. Many students carry out productive activities outside of lectures because of the free time to implement flexible online classes. So that Untirta Sociology Education students take advantage of their free time to carry out productive activities, such as teaching, tutoring, working part-time, or participating in internship program activities. These activities are carried out with each individual's goals to be achieved. Generally, the plan is to seek experience, relationships, and economic factors, namely, to earn money.